Structure, dynamics, and hydration of POPC/POPS bilayers suspended in NaCl, KCl, and CsCl solutions - Jurkiewicz, Piotr; Cwiklik, Lukasz; Vojtíšková, Alžběta; Jungwirth, Pavel; Hof, Martin (Biochimica et biophysica acta, 2012)
Effects of alkali metal chlorides on the properties of mixed negatively charged lipid bilayers are experimentally measured and numerically simulated. Addition of 20mol% of negatively charged phosphatidylserine to zwitterionic phosphatidylcholine strengthens adsorption of monovalent cations revealing their specificity, in the following order: Cs(+)<K(+)<Na(+). Time-resolved fluorescence solvent relaxation shows significant decrease both in mobility and hydration of the lipid carbonyls probed by Laurdan upon addition of the cations. The experimental findings are supported by molecular dynamics simulations, which show deep penetration of the cations down to the glycerol level of the lipid bilayer where they pair with oxygen atoms of carbonyl groups (with pairing with sn-2 carbonyl being about twice stronger than pairing with the sn-1 one). Moreover, the cations bridge neighboring lipids forming clusters of up to 4 lipid molecules, which decreases the area per lipid, thickens the membrane, causes rising of lipid headgroups, and hinders lipid dynamics. All these effects follow the same Hofmeister ordering as the cationic adsorption to the bilayer.
Keywords: Lipid Bilayers; chlorid sodný; Cesium; chloridy; Phosphatidylserines; Phosphatidylcholines; cesium; lipidové dvojvrstvy; chlorid draselný; fosfatidylseriny; Chlorides; Potassium Chloride; fosfatidylcholiny; Sodium Chloride